2018
DOI: 10.1186/s13063-018-2757-6
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of seroma following inguinal lymph node dissection with prophylactic, incisional, negative-pressure wound therapy (SEROMA trial): study protocol for a randomized controlled trial

Abstract: BackgroundRadical inguinal lymphadenectomy (ILND) for metastatic melanoma is associated with a high complication rate. Seroma is often the first postoperative complication, followed by prolonged wound healing sometimes requiring reoperation, infection, multiple outpatient visits and re-hospitalization. Prevention of seroma may, therefore, lead to a reduction in many of the other complications.Methods/designThe primary aim of this randomized study is to investigate whether fewer patients require treatment for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This prospective multicenter, randomized (1:1), open-labeled, parallel-group study was conducted in Denmark (four sites); at the Departments of Plastic Surgery at Odense University Hospital, Herlev Gentofte Hospital, Rigshospitalet, and Roskilde Hospital. The trial results herein were reported following the published trial protocol and the Consolidated Standards of Reporting Trials (CONSORT) statement 13 , 14 . All study data were collected and managed using REDCap (Research Electronic Data Capture) electronic data capture tools hosted at Odense University Hospital 15 , 16 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This prospective multicenter, randomized (1:1), open-labeled, parallel-group study was conducted in Denmark (four sites); at the Departments of Plastic Surgery at Odense University Hospital, Herlev Gentofte Hospital, Rigshospitalet, and Roskilde Hospital. The trial results herein were reported following the published trial protocol and the Consolidated Standards of Reporting Trials (CONSORT) statement 13 , 14 . All study data were collected and managed using REDCap (Research Electronic Data Capture) electronic data capture tools hosted at Odense University Hospital 15 , 16 .…”
Section: Methodsmentioning
confidence: 99%
“…It was initially planned to include 110 patients over a 3-year timeframe 13 . However, shortly before the trial was initiated, complete lymph node dissection was no longer performed routinely for micrometastatic disease in Denmark following the MSLT-II and DeCOG trial results 5 , 6 , 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported that one of the authors’ names is spelled incorrectly. In this Correction the incorrect and correct author name are shown.…”
Section: Correctionmentioning
confidence: 99%
“…At present, the piNPWT has been shown effective in improving wound healing in several surgical fields, reducing at the same time risks of complications even in other surgeries: inguinal dissection [17], mastectomy [18], ALT flap donor site [19], cesarean sections in highrisk patients [20,21]. Benefits from the piNPWT application have been reported in a case-control study in postbariatric abdominoplasty [21] and in cost-utility analysis [22].…”
Section: Introductionmentioning
confidence: 99%